Peran Bahasa Inggris sebagai Media Storytelling dalam Promosi Kuliner Tradisional Pematang Siantar untuk Mendukung Pariwisata Berkelanjutan - Sandra Maleachi; Rudy Pramono; Febryola Indra (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Pematangsiantar, a city in North Sumatra, offers a variety of attractive tourism potentials, including the famous Pematangsiantar Zoo, natural spring sources, and historical attractions such as the Siantar rickshaw, which uses a BSA motorbike. The city's traditional culinary offerings are also a major draw, with dishes like roasted pork, pork hong, and wonton noodles reflecting the richness of local culture. The role of the English language in the tourism industry is becoming increasingly important, especially in promoting Pematangsiantar's traditional culinary heritage to international tourists. This study aims to analyze the role of English-language narratives in promoting traditional cuisine and their contribution to the local economic growth, particularly in increasing the income of culinary entrepreneurs. The research method employed is a qualitative approach, utilizing participatory observation, in-depth interviews, and document analysis. The findings are expected to reveal effective strategies for utilizing English narratives to promote traditional cuisine, support the increase in tourist visits, and contribute to the economic growth of Pematangsiantar. This research aligns with the Sustainable Development Goals (SDGs), particularly in reducing poverty, improving quality education, and fostering inclusive and sustainable economic growth.